2014
DOI: 10.1007/s11356-014-3970-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum levels of 15 trace elements in breast cancer patients in Shandong, China

Abstract: Experimental and epidemiological studies suggest that serum levels of trace elements may be associated with breast cancer risk. We compared serum levels of 15 trace elements between breast cancer patients and normal controls from Shandong, China, for the first time to assess whether serum levels of trace elements were associated with breast cancer risk. Eighty-eight breast cancer patients and 84 healthy controls were enrolled in the study. A Spectraspan V direct current plasma atomic emission spectrometer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…In women with BC, the trace elements, cadmium, magnesium, copper, cobalt and lithium, were found in high levels. This suggests a possible association between serum levels of trace elements and breast cancer risk, however, this requires further investigation and if confirmed, the modulation of trace elements may help to reduce breast cancer risk (Ding et al, 2015).…”
Section: Dietary Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In women with BC, the trace elements, cadmium, magnesium, copper, cobalt and lithium, were found in high levels. This suggests a possible association between serum levels of trace elements and breast cancer risk, however, this requires further investigation and if confirmed, the modulation of trace elements may help to reduce breast cancer risk (Ding et al, 2015).…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Dietary factors associated with increased BC risk included intake of total n-6 polyunsaturated fatty acids (PUFA) (Kiyabu et al, 2015), vitamin D deficiency or insufficiency (Shi et al, 2014a;Park et al, 2015a), high levels of serum cadmium (Nagata et al, 2013;Itoh et al, 2014;Ding et al, 2015), high intake of salt (Park et al, 2014b), sugar (Sulaiman et al, 2014), meat (Ko et al, 2013), and saturated fat and oils (Balasubramaniam et al, 2013;Wang et al, 2013a). In women with BC, the trace elements, cadmium, magnesium, copper, cobalt and lithium, were found in high levels.…”
Section: Dietary Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some risk factors including early menarche, late menopause occurred, body mass index (BMI) and obesity after menopause, estrogen intake, alcohol consumption and tobacco use, exposure to ionizing radiation, and eating habits (3), as well as genetic (4)(5)(6), environmental factors (5,6), and ethnicity (7) can effect on the incidence of BC. In various studies, it was found that the serum levels of trace elements in patients with BC have changed and although their role is not fully understood, it may be associated with the risk of this disease (8). Zinc (Zn) is a vital mineral for the operation of numerous cellular processes and growth and may play an important role in malignancy etiology and outcome (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Larner et al have studied the isotopic compositions of Zn in breast cancer tissues and observed that breast cancer tumors are found to have a significantly lighter isotopic distribution of Zn than in blood, serum, and healthy breast tissues. Ding et al have analyzed the concentration levels of 15 trace elements such as Zn, Mn, Al, Cd, Fe, Mg, Ca, Pb, Cu, Se, Ni, Ti, Co, Li, and Cr in breast cancer patients in Shandong of China. They have observed that breast cancer patients have significantly higher serum levels of Cd, Mg, Cu, Co, and Li and significantly lower serum levels of Mn, Al, Fe, and Ti compared with their matched controls.…”
Section: Introductionmentioning
confidence: 99%